Perbandingan Karakteristik dan Fungsi Kata Keterangan Bahasa Mandarin dan Bahasa Indonesia - Ying, Yi (Humaniora, 2011)
Indonesian is an inflective language or functional language. It is a synthetic language, which is differentiated with agglutinative languages based on the inclination of morphemic formation of words. As a result, segmenting the elements is hard to be done. Mandarin as an isolative language is formed by singular morpheme. Synthetic language as the contrary consists of words of many morphemes. Mandarins’ and Indonesian’s grammatical function is as adverbs in most of the language occurrences. The difference between two adverbs is that in Mandarin, nouns and numbers cannot receive prefixes and suffixes. Mandarin’s adverbs in general are put in the beginning and middle of the words, which is different with Indonesian adverbs that can be placed in the end of the words.